2018
DOI: 10.1111/bph.14422
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of dopamine‐mediated firing inhibition through activation of the dopamine transporter in substantia nigra pars compacta neurons

Abstract: Our results indicate that the DAT plays a major role in DIR, mediating it under conditions of sustained dopamine exposure, and point to DAT as an important target for pharmacological therapies leading to prolonged enhancement of the dopaminergic signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 63 publications
1
16
1
Order By: Relevance
“…Recently, our research team has reported that a similar form of firing recovery may be obtained in response to DA, through an opposing depolarizing current generated by activation of the dopamine transporter (DAT). 21 According to literature, the possibility that the same mechanism may also underlie our present results is very unlikely. Indeed, for it to occur, DOPAquinone should activate and be uptaken by DAT, while products of DA oxidation-like quinones have been shown to inhibit rather than stimulate DAT.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Recently, our research team has reported that a similar form of firing recovery may be obtained in response to DA, through an opposing depolarizing current generated by activation of the dopamine transporter (DAT). 21 According to literature, the possibility that the same mechanism may also underlie our present results is very unlikely. Indeed, for it to occur, DOPAquinone should activate and be uptaken by DAT, while products of DA oxidation-like quinones have been shown to inhibit rather than stimulate DAT.…”
Section: ■ Results and Discussionmentioning
confidence: 59%
“…This perfusion time was selected to make sure that a clear steady-state level had been reached. 21 However, when DOPA-quinone 3 (300 μM) was added to the medium, still in the continuous presence of quinpirole, a partial recovery from firing inhibition was observed, attaining 81.85 ± 19.08% of control after 15 min, a value that was significantly different from that in quipirole alone (P < 0.01; F(2,12) = 15.99, n = 5; Figure 1). The possible desensitization of D2Rs by DOPA-quinone was ruled-out by looking at its effect on the GIRK-mediated response by GABA B receptor stimulation.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…Dopaminergic neurons signal through their canonical neurotransmitter, dopamine, at multiple release sites, notably through somatodendritic release via a calcium-dependent manner 64,85 . Furthermore, dopaminergic signalling occurs at multiple timescales 9,86 , selfsignaling 59,80,82,[87][88][89][90] , and mechanisms outside of receptor-dependent modulation of activity 59,62,91 . While dopaminergic neurons receive diverse inputs into their respective 7 regions, little is known about the self-organized intrinsic dopaminergic networks of the VTA and SNC.…”
Section: Resultsmentioning
confidence: 99%
“…Functional networks emerge from local interactions between neurons 46,47,49 . In dopaminergic networks, dopamine neurons have the machinery to directly interact through both synaptic and non-synaptic signaling 65,91,130 . However these studies do not account for dopaminergic network properties and dynamics, and how they differ by brain region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation